Subtle atomic group discrimination in the RNA minor groove - Frugier, Magali (The National Academy of Sciences of the USA, 1997)
As a problem in molecular recognition and for drug discovery, great interest has developed around the possibility that RNA structures could be discriminated by peptides and other small molecules. Although small peptides have been shown to have the capacity to discriminate specific bulges and loops in RNA molecules, discrimination of double helical regions by a peptide binder has not been reported. Indeed, the most accessible part of an RNA helix is the minor groove, and fundamental stereochemical considerations have suggested that discrimination of at least some base pairs would be difficult in the minor groove. Here we report the design and isolation of a peptide binder that manifests the most subtle kind of discrimination of base pair differences in the RNA minor groove. Functional discrimination of a single atomic group is demonstrated as well as the difference between two different angular orientations of the same group. This report of RNA helix discrimination by a peptide binder suggests a richer potential for RNA minor groove recognition than previously thought.